National Consumption of Antimicrobials in Tanzania: 2017–2019 - Mbwasi, Romuald; Mapunjo, Siana; Wittenauer, Rachel; Valimba, Richard; Msovela, Kelvin; Werth, Brian J.; Khea, Akida Msallah; Nkiligi, Emmanuel Alphonce; Lusaya, Edgar; Stergachis, Andy; Konduri, Niranjan (Frontiers in Pharmacology, 2020)
Objective: Surveillance of antimicrobial consumption is essential to the national action plan for antimicrobial resistance (AMR) as stipulated in the Global Action Plan on AMR and the Tanzanian National Action Plan on AMR. Given the paucity of antimicrobial consumption data in sub-Saharan Africa region, the objective of this study was to measure antimicrobial consumption in Tanzania. Methods: From 2017–2019, data on all antimicrobials imported into Tanzania were obtained from the Tanzania Medicines and Medical Devices Authority Data, augmented with purchasing data from the Medical Stores Department and data from local manufacturers. Data were collected and analyzed in accordance with the World Health Organization Anatomical Therapeutic Chemical and defined daily doses (DDD) methodology. Results: The average DDD per 1000 inhabitants per day (DDD/1000/D) for all antimicrobials was 80.8 ± 39.35. The DDD/1000/D declined from 136.41 in 2017 to 54.98 in 2018 and 51.02 in 2019. Doxycycline, amoxicillin, and trimethoprim-sulfamethoxazole were the most frequently consumed antibiotics during these years, accounting for 20.01, 16.75, and 12.42 DDD/1000/D, respectively. The majority of antimicrobial consumption in Tanzania occurred in the private sector, with the proportion of private-sector antibiotic consumption increasing annually from 2017 to 2019. Based on AWaRe classification >90% of antimicrobial consumption was Access class medications, with Watch and Reserve class medications accounting for <10% and <1% respectively. Conclusions: The private sector use of antimicrobials is significantly increasing and should be carefully monitored in accordance with national policies. Future work is necessary to increase reporting of antimicrobial consumption patterns in Sub-Saharan Africa.